Hand-Eye Coordination and Arm Muscles Explosive Power to Basketball Player’s Shooting - Neldi, Hendri; Sepriadi,; Apriyano, Berto; Hendri, Sherlyane; Kurnia Illahi, Bayu (International Journal of Psychosocial Rehabilitation, 2020)
The issue in this study is the shooting skills of basketball players, which are categorized as low. The aim of the study is to determine the relationship of hand-eye coordination and arm muscle explosiveness to the shooting ability of basketball players. This is correlational research design. Population is a group of basketball players at a school with 15 players as a sample who are taken by saturated sampling technique. The instruments used to collect the data are the following: (1) Ballwerfen und-Fangen is used to measure hand-eye coordination, (2) basketball throwing is used to measure arm muscle explosive power, and (3) one-handed penalty shooting is used to measure the shooting ability of a basketball player. The data were analyzed by using statistic analysis of Pearson Product-Moment to see whether two independent variables were related to the dependent variable with a significant level of α=0.05. The result of the research showed that (1) there was a significant correlation between hand-eye coordination and shooting ability (r=0.657 with tobserved=3,258 > ttable=2,145), (2) there was a significant correlation between arm muscle explosive power and shooting ability (r=0.712 with tobserved=3,794 > ttable=2,145), and (3) there was a significant correlation between hand-eye coordination and arm muscle explosiveness to the shooting ability (R=0.747 with Fobserved 8,206 > Ftable 3,880).